Work of the Cochrane Bone, Joint and Muscle Trauma Review Group: making sense of complexity. Issue 4 (November 2013) - Handoll, Helen
Abstract This article examines the ways in which members of the Cochrane Bone, Joint and Muscle Trauma Review Group have tackled the intrinsic complexity of a large clinical area. This features a diversity of injuries in people of all ages, predominantly physical and surgical interventions that are inherently complex interventions, and a huge array of outcome measures. The methods described include a purposeful focus on common injuries, such as fragility fractures in older people; and the generation of groups of "all intervention" reviews whose structure is informed by a systematic approach, incorporating knowledge of clinical pathways and categorization of interventions. The article concludes with some thoughts about the challenges ahead, particularly in terms of selecting the scopes of future reviews.